Kolaborasi Edukatif untuk Masa Depan Desa: Sosialisasi Bahaya Narkoba dan Pengembangan Pertanian bagi Kelompok Wanita Tani Desa Taman, Bali - Sri Ratna Dewi; Putu Indah Budi Apsari; Ni Putu Diah Witari (JURNAL SEWAKA BHAKTI, 2026)
This community service activity is one of the implementations of the Regular KKN-PMM Period II 2025 activities which were held on July 20 - August 25, 2025 with KKN locations spread across several areas, one of which was in Taman Village, Abiansemal, Badung. The KKN-PMM activity in Taman Village which was attended by 23 students from Warmadewa University found several problems faced, namely community unrest regarding drug problems and the less than optimal use of manure as well as the lack of understanding of the Women Farmers Group regarding effective and environmentally friendly land processing techniques. Therefore, on this occasion, socialization activities were carried out on the dangers of drug abuse to all levels of society, as well as education on land processing and the provision of plant seeds to the Women Farmers Group. The drug socialization aims to increase public awareness of the negative impacts of drugs on health, family, and social life. Meanwhile, agricultural education activities aim to empower Women Farmers Group in supporting food security and family economic independence through simple agricultural practices. Activity methods include counseling, interactive discussions, and direct practice in the field. The results of the activity indicate an increase in community knowledge about the dangers of drugs, as well as growing interest and skills among Women Farmers Group members in agricultural land management. This educational collaboration is expected to be the first step in building a healthy, productive, and independent village.